The social reality of Europe after the crisis: trends, challenges and responses - Diamond, Patrick; Liddle, Roger; Sage, Daniel (London, 2015)
"The economic crisis of recent years continues to have a profound effect on the lives of European citizens. Economically, politically and socially, the crisis has led to fundamental change for many people's lives. As well as creating new concerns, the crisis has simultaneously exacerbated existing ones, raising profound challenges to the sustainability and success of the European model. This book seeks to examine this new 'social reality' of post-crisis Europe, exploring what both the EU and national governments can do to restore its strength, sustainability, cohesion and competitiveness."